Preventive Care for Adults With Cerebral Palsy and Other Neurodevelopmental Disabilities: Are We Missing the Point? - Whitney, Daniel G.; Rabideau, Michelle L.; McKee, Michael; Hurvitz, Edward A. (Frontiers in Integrative Neuroscience, 2022)
Preventive care techniques are cornerstones of primary care for people with neurodevelopmental disabilities such as cerebral palsy (CP). However, well-established methods evaluating health constructs may not be applied in the same way for adults with CP, as compared to the general population, due to differences in anatomy/physiology, leading to missed opportunities for interventions, medication modifications, and other primary/secondary prevention goals. One barrier to care prevention comes from misinterpretation of values to capture health constructs, even when measurements are accurate. In this Perspective, we emphasize the need for differential interpretation of values from commonly used clinical measures that assess for well-known medical issues among adults with CP- obesity risk, bone health, and kidney health. We provide technical, but simple, evidence to showcase why the underlying assumptions of how some measures relate to the health construct being assessed may not be appropriate for adults with CP, which may apply to other neurodevelopmental conditions across the lifespan.